Knowledge and Awareness Regarding Defining Components of Research Process among Dental Graduates: Defining Components of Research Process among Dental Graduates - Tariq , Shanzay; Alamgir, Wajiha; Haider, Adeel; Jabbar, Uzma; Javaid, Maheen; Chaudhary, Fatima (Pakistan Journal of Health Sciences, 2022)
Modern breakthroughs significantly improve life span and quality. Conducting research should be viewed as crucial to medical education. Critical thinking and reasoning abilities must be developed if dental practitioners are to embrace a positive viewpoint of scientific study. Therefore, efforts are being made for graduate dentists to bridge gap between understanding research process and its components. Objectives: To determine how well dental graduates understood key elements of research process. Decisions and curriculum changes for bettering knowledge and conducting research could be made using study’s findings. Methods: A cross-sectional descriptive study was designed and conducted among house officers of University Dental Hospital, University of Lahore. Self-administered questionnaire was designed and circulated among various dental schools in area. For data analysis, SPSS Version 25.0 was used. Results: Total of 161 participants took part in current study out of which majority (n=107, 66.4%) were females and minority (n=54, 44.6%) were males with the age group lying between 23-25 years. Bulk of study participants (n= 53, 32.9%) rarely had any experience in research. Participants indicated that they were knowledgeable about research and its components, scoring 48% fair, 16% good, and 6% excellent, although 30% of them showed inadequate understanding. Conclusions: The majority of dental graduates believed they had poor to fair knowledge of how to plan, carry out, and write a research project